2013
DOI: 10.1121/1.4816552
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different analysis techniques and recording duty cycles on passive acoustic monitoring of killer whales

Abstract: Killer whales in British Columbia are at risk, and little is known about their winter distribution. Passive acoustic monitoring of their year-round habitat is a valuable supplemental method to traditional visual and photographic surveys. However, long-term acoustic studies of odontocetes have some limitations, including the generation of large amounts of data that require highly time-consuming processing. There is a need to develop tools and protocols to maximize the efficiency of such studies. Here, two types… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 37 publications
5
11
0
Order By: Relevance
“…The acoustic presence of the focal species was increasingly underestimated with decreasing duty cycles. These findings match the trends observed by Riera et al (2013), showing that a duty cycle of 1 3 resulted in a 24% decline in encounter detections of killer whale calls and a consequent underestimation of the time whales were acoustically present in the data set compared to a larger duty cycle of 2…”
Section: Discussionsupporting
confidence: 87%
“…The acoustic presence of the focal species was increasingly underestimated with decreasing duty cycles. These findings match the trends observed by Riera et al (2013), showing that a duty cycle of 1 3 resulted in a 24% decline in encounter detections of killer whale calls and a consequent underestimation of the time whales were acoustically present in the data set compared to a larger duty cycle of 2…”
Section: Discussionsupporting
confidence: 87%
“…Predictably, any reduction in recording effort over a given monitoring period will lead to underestimation of species presence, except for those that are continuously present and acoustically active (Riera et al, 2013;Thomisch et al, 2015). The results presented here demonstrate that frequent, short listening periods provide a more accurate assessment of daily presence than longer, less frequent periods, even when the overall amount of recording effort is lower.…”
Section: Discussionmentioning
confidence: 61%
“…Shortening subsampling periods resulted in increasingly underestimated detection rates of rails. Previous studies reported similar trends where subsampling one‐third of the killer whale ( Orcinus orca ) calls led to a 24% decline in detections (Riera et al ) and subsampling less than one‐tenth of the North American right whale ( Eubalaena glacialis ) calls resulted in a reduction in acoustic presence up to 26% (Thomisch et al ). These findings demonstrate the importance of understanding tradeoffs between subsampling duration and estimation biases prior to the analysis of acoustic data.…”
Section: Discussionmentioning
confidence: 61%